2021
DOI: 10.3390/app11177767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Yeast Strain on Odor-Active Compounds in Fiano Wine

Abstract: The type of yeast strain used for wine alcoholic fermentation dramatically affects its final volatile composition and, therefore, its sensory properties. In this study, the influence of four oenological Saccharomyces strains (three S. cerevisiae and one S. bayanus) on wine volatile composition was determined on the Fiano variety, a typical cultivar from the Campania region (Italy), fermented in oak barrique. Fiano wines were analyzed by means of gas chromatography/mass spectrometry (GC/MS) and gas chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
5
1
Order By: Relevance
“…A similar mismatch is seen in the concentration of diethyl butanoate, a carrier of fruity and caramel aromas. In Plavac Mali wines maximum of this compound was in N wines, and the minimum in S wines, contrary to data previously reported [33]. Differences between esters are related to a yeast strain but also to grape juice components [35] and juice composition as sugar content, YAN levels, amino acid profile, carbon and nitrogen content, temperature, and aeration degree during vinification [6,43].…”
Section: Fermentation Aroma Compounds In the Plavac Mali Wines Produc...contrasting
confidence: 70%
See 1 more Smart Citation
“…A similar mismatch is seen in the concentration of diethyl butanoate, a carrier of fruity and caramel aromas. In Plavac Mali wines maximum of this compound was in N wines, and the minimum in S wines, contrary to data previously reported [33]. Differences between esters are related to a yeast strain but also to grape juice components [35] and juice composition as sugar content, YAN levels, amino acid profile, carbon and nitrogen content, temperature, and aeration degree during vinification [6,43].…”
Section: Fermentation Aroma Compounds In the Plavac Mali Wines Produc...contrasting
confidence: 70%
“…Yeasts differ in the capability of the detachment of those compounds in dependence on the chemical structure of the sugar and the aglycone moieties [33]. Acid hydrolysis plays an important role in the rearrangements of terpenes and C13 norisoprenoids.…”
Section: Varietal Aroma Compounds In the Plavac Mali Wines Produced B...mentioning
confidence: 99%
“…The Lt x Sc (J) treatment resulted in the highest concentration of total lactones (590 µg/L), while the lowest concentration of 251 µg/L was determined in (K (J)). The most represented lactones in wine are butyrolactone and γ-butyrolactone [62]. This study found a significant increase in γ-butyrolactone in Lt x Sc (J), which is consistent with previous reports [46,51].…”
Section: Volatile Aromatic Compounds In Winessupporting
confidence: 92%
“…The special aromatic character of Muscat of Alexandria wines is attributed to the presence of terpenes and C13-norisoprenoids in concentrations higher than their odor threshold; such volatile molecules originate from grapes [ 44 ]. The major fermentation compounds, produced due to the metabolic activity of the yeasts, are alcohols, ethyl esters, acetates, and fatty acids [ 45 ]. Many primary and secondary volatile metabolites have been detected, identified, and semi-quantified with the described HS-SPME-GC-MS method, and a characteristic chromatogram of the 1st day of fermentation is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%